Training and development practice in Coats Bangladesh Ltd: a study on the impact of employee development - Mohsin, Mushrath Binthe (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.